Farms versus firms in economic development: The assumptions and consequences of learning dynamics in agriculture and mnufacturing - Smita Srinivas; José Eustáquio Ribeiro Vieira Filho (Institute for Applied Economic Research (ipea), 2015)
Economic development theories and their learning frameworks differently address farms and firms. This article argues that the traditional double-standard of the primacy of manufacturing rests on a debatable stages model that under-recognizes learning and innovation in agriculture and its crossover supplier segments with manufacturing. The sections analyze manufacturing bias; demand's effects; and differences in the technological process and links between agriculture and manufacturing. It then analyzes the learning implications of two theories - unlimited labor and induced innovation - on economic development. The article concludes with the implications of the distinctive learning dynamics within and between farms and firms. An evolutionary approach has potential for understanding both manufacturing as well as agriculture, but should be more carefully extended to consider the inter-linkages between the two to extract the maximum developmental benefit. It is clear that models that connect learning and innovation to growth require closer attention and have important developmental consequences through policy design.
Keywords: O3; O4; Q16; 330; agriculture; industry; economic development; learning and innovation